Application and exploration of interprofessional education in the teaching of plastic and reconstructive surgery: a narrative review - Yingfei Sun; Jiayi Mao; Yinghong Su; WenZheng Xia; Qingfeng Li; Tao Zan (BMC Medical Education)
Abstract The growing discussion on "interdisciplinary integration" brings attention to the "interprofessional education" (IPE) in the field of plastic surgery. IPE not only improves the precision and effectiveness of plastic and reconstructive surgery but also plays an important role in personalized treatment. Whereas, the implementation of IPE in plastic and reconstructive surgery field faces huge difficulties such as technology combination, standard making, and lacking of qualified talents. This article individually summarizes the latest developments in the integration of plastic and reconstructive surgery with engineering, basic science, and human science. It looks forward to the future practice and innovation of IPE in the field of plastic and reconstructive surgery, analyzes the challenges in cultivating innovative professional talents, and proposes methods to overcome these difficulties in a way that invites further discussion.